Controlling Stress: A Conceptual Update - Hiebert, Bryan (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper presents an update of an earlier framework for controlling stress. A contemporary interactional conceptualization of stress is presented and some inadequacies of earlier perspectives are outlined. This is followed by a model for stress control that includes controlling stress by acquiring better skills for dealing with environmental demands.